Identification of effective sources for spot blotch and stripe rust in barley - Goyal, Vishnu Kumar; Shekhawat, Pradeep Singh; Vishwakarma, Siya Ram; Bhardwaj, Subhash Chander; Kumar, Sudheer; Kharub, Ajit Singh; Singh, Gyanendra Pratap (Journal of Cereal Research, 2025)
Stripe rust and spot blotch are major biotic constraints in yield maximization in barley. Stripe rust is caused by fungus, Puccinia striiformis f. sp. hordei and wide spread in northern hills, foot hills and in the states of Punjab, Haryana and Rajasthan. Spot blotch (Bipolaris sorokiniana) is one of the major diseases in north eastern Indo-Gangetic plains having warm and humid climate. The resistant sources for stripe rust are available but the genetic resources for spot blotch are indeed meagre. Therefore, the present investigation was carried out to identify combined sources for stripe rust and spot blotch in barley. The experiments for stripe rust were conducted at Durgapura and Karnal during 2015-16 to 2017-18. While, spot blotch evaluation was carried out for two years at Faizabad and Karnal centres during 2015-16 and 2016-17. The indigenous genotypes namely DWRB127, DWRB128, DWRB136, DWRB137, DWRB143, RD2786 and Dolma showed resistance for stripe rust. Based upon stripe rust and spot blotch reactions the genotypes namely, DWRB136, Notch-2, Orosus and Bella Union were found promising. Similarly, the cross combination viz., Lbiran/Una80//Lignee640/3/Bbsc/4/Chamico and P.sto/3/Libran/Una80//Lignee640/4/Bllu/5/ Petunia1 were also considered promising for barley stripe rust and spot blotch. Therefore, these identified genotypes are suggested to be incorporated in future barley breeding programmes for gainfully utilization.DOI.10.25174/2582-2675/2020/88973